ANALISIS PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP MATA PELAJARAN ESTIMASI BIAYA KONSTRUKSI DI SMK JURUSAN DPIB - Ar Razi Atsil Wabahey (ADIBA : JOURNAL OF EDUCATION, 2024)
The importance of competency in estimating construction costs shows how important vocational education is, especially at DPIB vocational high schools, in preparing students to enter the world of work. One of the most important skills in the construction industry is the ability to estimate construction costs, which requires a deep understanding of various aspects of a project as well as the integration of theory and practice. This research aims to evaluate the influence of the Project Based Learning (PjBL) learning model on construction cost estimation subjects in the Building Information Modeling Design (DPIB) environment. The method used is a literature review which involves the analysis of several journals and articles that are relevant to the specified topic. The results of a comprehensive analysis show the positive impact of using the Project Based Learning learning model on learning the subject of construction cost estimation. The research results confirm that the Project Based Learning Model is effective in improving students' critical and creative thinking abilities as well as overall learning effectiveness. Therefore, the Project Based Learning Model can be considered as a relevant solution to improve student learning outcomes, especially in the subject matter of Construction Cost Estimation in Vocational Schools.